Footwear soles friction on steel and tile surfaces: Experiments and modeling - Lasse Jakobsen; Avinash Tiwari; Ion Marius Sivebaek; Bo Persson (Friction, 2025)
Understanding and modeling the friction between footwear soles and substrates is important to avoid slips. In this study, we measure the friction force for three different footwear soles sliding on steel and tile surfaces. We use a vulcanized rubber (RU), a thermoplastic polyurethane (TPU), and a polyurethane (PU) compound. The viscoelastic properties of the elastomers are fully characterized using dynamic mechanical analysis (DMA). The surface roughness power spectra of the substrates (steel and tile) are obtained from stylus topography measurements. The friction force is measured as a function of sliding velocity using two different tribometers. We apply Persson’s multiscale contact mechanics theory, with the substrate surface roughness power spectrum and the elastomer viscoelastic properties as input, to model the friction.